Weight gain since menopause and its associations with weight loss maintenance in obese postmenopausal women - Sénéchal M (Clinical Interventions in Aging, 2011)
M Sénéchal1,2, H Arguin6, DR Bouchard4,5, AC Carpentier3, JL Ardilouze3, IJ Dionne1,2, M Brochu1,21Research Centre on Aging, Health and Social Services Centre, University Institute of Geriatrics of Sherbrooke, 2Faculty of Physical Education and Sports, University of Sherbrooke, 3Clinical Research Centre, Sherbrooke University Hospital Centre, Sherbrooke, QC; 4Faculty of Kinesiology and Recreation Management, University of Manitoba, Winnipeg, MB; 5Health, Leisure & Human Performance Research Institute, Winnipeg, MB; 6Division of Kinesiology, Department of Social and Preventive Medicine, Faculty of Medicine, Laval University, QC, CanadaObjective: To examine the association between weight gain since menopause and weight regain after a weight loss program.Methods: Participants were 19 obese women who participated in a 15-week weight loss program and a 12-month follow-up. Main outcomes were: body composition, resting metabolic rate, energy intake, energy expenditure, and weight regain at follow-up.Results: All body composition measures significantly decreased after intervention (all P ≤ 0.01) while all measures of fatness increased significantly after the 12-month follow-up (P ≤ 0.01). Body weight gain since menopause was associated with body weight regain (r = 0.65; P = 0.003) after follow-up even after adjustment for confounders.Conclusion: Weight gain since menopause is associated with body weight regain following the weight loss program. Therefore, weight gain since menopause should be considered as a factor influencing weight loss maintenance in older women.Keywords: obesity, body weight, weight regain, postmenopausal women, aging